PERSEPSI MASYARAKAT TENTANG DAMPAK AKTIFITAS PT.SEMEN PADANG DI KELURAHAN INDARUNG KECAMATAN LUBUK KILANGAN KOTA PADANG - Sulastri, Rina; Hermon, MP, Dr. Dedi; Juita, S.Pd., M.Si, Erna (Pendidikan Geografi, 2014)
ABSTRACT This study aims to obtain data and information on the Public Perception About Impact of Activity in Padang PT.Semen Indarung Urban District of Lubuk Kilangan Padang, of : 1 ) health, 2 ) cleanliness of the residence, 3 ) public yard, 4 ) infrastructure. This research is a descriptive study. Population of the study was the people in Indarung Lubuk Kilangan District of Padang . Sample was 77 families and By using proposive sampling technique. The results of this the study : 1 ) the public perception about the impact of activities PT.Semen Padang viewed from health , included less well with the percentage of 59.78 %. This means that the people in Indarung argue that PT.Semen Padang activity does not interfere with public health , as for the people who complain their health impaired people who are close to the plant. 2 ) Public perception about the impact of PT.Semen Padanga can be activity seen from good hygiene with percentage of 79.81 % . This means that people argue that the cleanliness of the community residence has been disturbed by the activities of PT.Semen Padang. 3 ) Public perception about  the impact of activities PT.Semen Padang viewed of the yard is quite good with a percentage of 76.84 % . This means that people argue that PT.Semen  Padang  activities has made people yard become dirty and 4 ) Public perception about activities of  PT.Semen Padang can be seen from infrastructure is quite good with a percentage of 71.94 % . This means that the public argue that the activity of PT.Semen Padang have  been fouled the  infrastructure in the  Indarung Lubuk Kilangan district of Padang